Peningkatan Motivasi Belajar Siswa Pada Pembelajaran Pendidikan Pancasila Melalui Model Pembelajaran Make A Match Di Kelas IV Sekolah Dasar - Salsa Mutiara Ningsih; Selfia Fitri; Wandri Ramadhan (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2026)
One important element that affects students’ success in the educational process is their motivation to learn. Nevertheless, in Pancasila Education classes at SDN 14 Tanjung Barulak, students exhibited low learning motivation, characterized by limited engagement during lessons, minimal participation in classroom activities, and a lack of enthusiasm when completing assignments. This study sought to determine whether the Make A Match learning paradigm may increase students' motivation to learn. A quantitative pre-experimental approach utilising a One Grup Pretest-Posttest Design was employed. A saturation sampling technique was used to choose 19 fourth graders as participants. Data was gathered via observation sheets, learning motivation surveys, and documentation. The data was evaluated using descriptive statistics and a paired sample t-test. The average motivation score increased by 23.94 points, from 53.95 in the pretest to 77.89 in the posttest, according to the results. The hypothesis test revealed a statistically significant change in students' motivation to study before and after the implementation of the Make A Match learning paradigm, with a significance value of 0.000 (<0.05). These results imply that the Make A Match methodology increases students' motivation to acquire Pancasila Education by creating a more engaging, cooperative, and joyful learning environment. As a result, the learning model Make A Match can be regarded as a successful teaching method for raising primary school pupils' motivation to learn.